Determination of albendazole, fenbendazole, and their metabolites in mouse plasma by high performance liquid chromatography using fluorescence and ultraviolet detection - Rummel, N.; Chung, I.; Shaikh, B. (2011)
A rapid and reliable high performance liquid chromatographic (HPLC) method has been developed and validated for the determination of albendazole (ABZ), albendazole sulfoxide (ABZSO), albendazole sulfone (ABZSO(2)); fenbendazole (FBZ), fenbendazole sulfoxide (FBZSO), and fenbendazole sulfone (FBZSO(2)) in mouse plasma. The mouse plasma was made alkaline with potassium carbonate and extracted with ethylacetate. The extracts were evaporated, reconstituted in mobile phase, and analyzed by HPLC. The chromatography was carried out on a reversed-phase column using acetonitrile-methanol-buffer as the mobile phase. The fenbendazole and its metabolites were detected by using UV detector set at the wavelength of 290 nm. The albendazole and its metabolites were detected by a fluorescence detector with excitation and emission wavelengths of 290 and 330 nm, respectively. The average recoveries of ABZ, ABZSO, and ABZSO(2) from fortified control plasma samples were 95, 82, and 92, respectively. Similarly, the average recoveries of FBZ, FBZSO, and FBZSO(2) were 64, 90, and 94, respectively. The average CVs were <= 15 for all of the compounds. The method was applied to incurred mouse plasma samples to determine ABZ, FBZ, and their metabolites.